A method for preparing an aluminum-based alloy powder for 3D printing with surface-embedded reinforcing particles
Patent Information
- Application Number
- CN202611341289.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本发明的目的是提供一种解决上述纳米粉末团聚与球磨引入杂质的问题,促使纳米颗粒增强相均匀分布于铝合金粉末表面进行改性提高激光吸收率的方法
(1)本发明结合三维混料预混合和声学共振混合对混合粉末进行双混合,通过预混合对纳米增强相颗粒进行搅拌摩擦予以一定程度上分散,并可将大部分黏附于铝合金粉末表面;声学共振混合则将预混合粉末置于宏观共振对流与微观声流剪切的双重耦合混合环境中,物料在整个容器内做整场的混合运动,从而实现纳米增强相颗粒在Al合金粉末表面的均匀分布。
Smart Images

Figure CN122999992A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metal additive manufacturing technology, specifically relating to a method for preparing aluminum-based alloy powder for 3D printing with reinforcing particles embedded on its surface. Background Technology
[0002] Additive manufacturing of aluminum alloys combines the advantages of integrated forming of complex components using additive manufacturing with the low density, high strength, and excellent oxidation resistance and thermal conductivity of aluminum alloys, making them a widely used lightweight metallic structural material in aerospace, automotive, and electronics industries. However, the urgent need for higher performance in key structural materials presents greater challenges to improving the performance of aluminum alloys. Numerous studies have shown that introducing nano-reinforcing phases can act as grain growth inhibitors, and their intragranular boundary distribution can effectively hinder dislocations. Combined with their inherent superior properties, this can effectively improve the overall performance of aluminum alloys.
[0003] Currently, the main heat source for additive manufacturing of aluminum alloys is a high-energy laser beam. This leads to problems such as high energy loss due to the high reflectivity of aluminum alloys, insufficient heat input, and the formation of powder incomplete fusion and porosity defects in the formed parts. Furthermore, due to its high thermal conductivity and face-centered cubic structure... <100> Orientation is the preferred growth direction, therefore it is easy to form along the construction direction during laser forming. <100> The presence of coarse, columnar grains with specific orientations leads to severe anisotropy in the formed parts. In recent years, numerous studies have shown that surface modification of aluminum alloy powder is an effective way to reduce the laser reflectivity of aluminum alloys, including the addition of nano-reinforcing phases and surface etching. Considering the high demands on service performance, the addition of nano-reinforcing phases is a highly promising surface modification method. Furthermore, nano-reinforcing phases can provide a certain degree of undercooling, acting as heterogeneous nucleating agents to effectively promote the formation of equiaxed grains, thereby optimizing the overall properties of the aluminum alloy.
[0004] Currently, the main methods for adding nano-reinforcing phases to spherical metal powders are three-dimensional mixing and ball milling. Due to the high surface energy of nanoparticles, agglomeration easily occurs during these two mixing methods, leading to uneven microstructure in the final formed part and affecting its overall performance. Furthermore, ball milling can introduce impurities and damage the spheres, resulting in low laser forming quality and impaired mechanical properties. Summary of the Invention
[0005] The purpose of this invention is to provide a method for solving the problems of nanoparticle agglomeration and impurities introduced by ball milling, and for promoting the uniform distribution of nanoparticle reinforcing phase on the surface of aluminum alloy powder to modify and improve laser absorption rate.
[0006] To achieve the above-mentioned objectives, a method for preparing aluminum-based alloy powder for 3D printing with reinforcing particles embedded on its surface is proposed, the specific steps of which are as follows: Step 1: Weigh a certain proportion of matrix aluminum alloy component powder and nanoparticle reinforcing phase component powder, wherein the mass fraction ratio of the matrix aluminum alloy component powder and the nanoparticle reinforcing phase component powder is (95.0%~99.5%):(0.5%~5%). Step 2: Place the matrix aluminum alloy component powder and nanoparticle reinforced phase component powder weighed in Step 1 into a three-dimensional mixer, add zirconia balls with an average particle size of 5mm at a ball-to-particle ratio of 0.5~1.5:1, fill the tank with protective gas, and then mix at a frequency of 24Hz for 1~3h. After the mixing process is completed, separate the mixed powder from the grinding balls. Step 3: Place the mixed powder obtained in Step 2 into an acoustic resonance mixing container, add auxiliary hard balls at a ball-to-powder ratio of 0.4:1, fill the container with protective gas, and then mix for 8-15 minutes under an acceleration of 50-75g, achieving a resonance frequency of 60-70Hz. Step 4: Separate the acoustic resonance mixed powder from the grinding balls to obtain the target powder.
[0007] Furthermore, the aluminum alloy of the matrix component is selected from one of the following: 1-series aluminum alloys, 2-series aluminum alloys, 3-series aluminum alloys, 4-series aluminum alloys, 5-series aluminum alloys, 6-series aluminum alloys, 7-series aluminum alloys, 8-series aluminum alloys, and 9-series aluminum alloys; the nanoparticle reinforcing phase component is selected from one or more of the following: TiB2, LaB6, ZrC, B4C, SiC, TiC, WC, Al3BC, AlN, TiN, Si3N4, Al2O3, Y2O3, TiO2, SiO2, ZrO2, MgO, and diamond.
[0008] Furthermore, in step one, the particle size of the matrix aluminum alloy component powder is 15~53μm, and the particle size of the nanoparticle-reinforced phase component powder is below 200nm.
[0009] Furthermore, in step two, the protective gas is argon.
[0010] Furthermore, in step three, the auxiliary hard spheres are one or more of tungsten, tungsten carbide, and zirconium oxide, with a particle size of 0.3~2 mm.
[0011] Furthermore, in step three, the auxiliary hard spheres are composed of high-density tungsten spheres or tungsten carbide spheres and low-density zirconium oxide spheres, wherein the mass fraction ratio of high-density hard spheres to low-density hard spheres is 10~20%:80~90%.
[0012] Furthermore, in step three, the protective gas is argon.
[0013] In this invention, the separation of the mixed powder and the grinding balls is carried out by conventional sieving.
[0014] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention combines three-dimensional mixing premixing and acoustic resonance mixing to perform dual mixing of the mixed powder. The premixing disperses the nano-reinforcing phase particles to a certain extent by stirring and friction, and most of them can adhere to the surface of the aluminum alloy powder. The acoustic resonance mixing places the premixed powder in a dual coupling mixing environment of macroscopic resonance convection and microscopic acoustic flow shearing. The material undergoes a whole-field mixing motion in the entire container, thereby achieving uniform distribution of nano-reinforcing phase particles on the surface of Al alloy powder.
[0015] This invention incorporates auxiliary hard spheres into the acoustic resonance mixing process. Due to the difference in particle size and density between the auxiliary hard spheres and the premixed powder, they can micro-impact the surface of the mixed powder during the acoustic resonance mixing process. Firstly, by utilizing the micro-shearing effect of the acoustic resonance mixing technology, satellite powder and hollow powder on the surface of the aluminum alloy powder can be destroyed, ensuring the purity of the aluminum alloy powder. Secondly, under the impact, the hard nano-reinforcing particles are adhered to and embedded on the surface of the soft aluminum alloy powder, thereby enhancing the mechanical connection between the nano-reinforcing particles and the aluminum-based powder, thus improving the flowability of the mixed powder and improving the quality of additive manufacturing.
[0016] The hard spheres selected in this invention have a larger particle size than aluminum alloy powder. On the one hand, the larger particle size of the hard spheres can provide sufficient impact and shear energy to effectively deagglomerate the nanoparticles to the submicron or even nanoscale. On the other hand, it can improve batch processing efficiency and facilitate sieving.
[0017] (4) The aluminum-based alloy powder for 3D printing with reinforcing particles embedded on the surface prepared by the present invention has nano reinforcing particles uniformly embedded on the surface of aluminum alloy powder, which can significantly improve the absorption rate of the powder to laser, reduce the energy consumption of laser forming, improve the forming quality of additive manufacturing, and ensure that the printing process is stable and reliable.
[0018] (5) The preparation process of the present invention is simple, with no special equipment or tooling requirements, and can be industrialized using conventional powder metallurgy equipment. Attached Figure Description
[0019] Figure 1 SEM image of 0.5 wt.% ZrO2 / AlSi10Mg mixed powder prepared in Example 1; Figure 2 SEM image of 3wt.% TiC / CF530I mixed powder prepared in Example 2; Figure 3 SEM image of 5 wt.% ZrO2 / AlSi10Mg mixed powder prepared in Example 3; Figure 4FIB-SEM images of 5 wt.% ZrO2 / AlSi10Mg mixed powder prepared in Example 3 ((a) low magnification, (b) high magnification). Figure 5 SEM image of 0.5 wt.% ZrO2 / AlSi10Mg mixed powder prepared in Comparative Example 1 Figure 6 SEM image of 0.5 wt.% ZrO2 / AlSi10Mg mixed powder prepared in Comparative Example 2 Figure 7 SEM image of 0.5 wt.% ZrO2 / AlSi10Mg mixed powder prepared in Comparative Example 3 Figure 8 SEM image of 15 wt.% ZrO2 / AlSi10Mg mixed powder prepared in Comparative Example 4 Figure 9 SEM image of 0.5 wt.% ZrO2 / AlSi10Mg mixed powder prepared in Comparative Example 5 Detailed Implementation
[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] Example 1 Prepare 0.5wt.% ZrO2 / AlSi10Mg mixed powder with a thickness of 15–53 µm for 3D printing.
[0022] According to the mass ratio of ZrO2:AlSi10Mg = 0.5:99.5, 5g of ZrO2 particles with an average particle size of 20nm and 995g of AlSi10Mg powder with a particle size range of 15-53µm were weighed. The weighed AlSi10Mg powder and nano ZrO2 particles were placed in a three-dimensional mixer, and zirconia balls with an average particle size of 5mm were added at a ball-to-particle ratio of 0.5:1. Argon gas was introduced into the container for 1 minute, followed by mixing at a frequency of 24Hz for 2 hours. After the mixing process, the mixed powder was separated from the grinding balls. The mixed powder was placed in an acoustic resonance mixing container, and auxiliary hard balls with an average particle size of 0.3mm were added at a ball-to-particle ratio of 0.4:1, wherein the mass fraction ratio of tungsten balls to zirconia was 10%:90%. Argon gas was introduced into the container for 1 minute, followed by mixing for 10 minutes at an acceleration of 50g and a resonant frequency of 60Hz. After mixing, the mixed powder was separated from the grinding balls to obtain nanoparticle-modified aluminum alloy powder for 3D printing. Finally, the laser absorptivity of the mixed powder was measured. The morphology and properties of the spherical powder of this particle-reinforced aluminum matrix composite for 3D printing are as follows: Figure 1 As shown in Table 1.
[0023] Table 1. Properties of the 15–53 µm 0.5 wt.% ZrO2 / AlSi10Mg mixed powder prepared in Example 1 <![CDATA[0.5wt.%ZrO2 / AlSi10Mg]]> 1.45 89 27 Example 2
[0024] Prepare 3wt.% TiC / CF530I mixed powder with a thickness of 15–53 µm for 3D printing.
[0025] According to a mass ratio of TiC:CF530I = 3:97, 30g of TiC particles with an average particle size of 50nm and 970g of CF530I powder with a particle size range of 15-53µm were weighed out. The weighed CF530I powder and nano-TiC particles were placed in a three-dimensional mixer, and zirconia balls with an average particle size of 5mm were added at a ball-to-particle ratio of 1:1. Argon gas was introduced into the container for 1 minute, followed by mixing at a frequency of 24Hz for 3 hours. After the mixing process, the mixed powder was separated from the grinding balls. The mixed powder was placed in an acoustic resonance mixing container, and auxiliary hard balls with an average particle size of 0.5mm were added at a ball-to-particle ratio of 0.4:1, wherein the mass fraction of tungsten balls to zirconia was 15%:85%. Argon gas was introduced into the container for 1 minute, followed by mixing for 8 minutes at an acceleration of 60g and a resonant frequency of 65Hz. After mixing, the mixed powder was separated from the grinding balls to obtain nanoparticle-modified aluminum alloy powder for 3D printing. Finally, the laser absorptivity of the mixed powder was measured. The morphology and properties of the spherical powder of this particle-reinforced aluminum matrix composite for 3D printing are as follows: Figure 2 As shown in Table 2.
[0026] Table 2. Properties of the 15–53 µm 3 wt.% TiC / CF530I mixed powder prepared in Example 2 3wt.%TiC / CF530I 1.50 83 7 Example 3
[0027] Prepare 5wt.% ZrO2 / AlSi10Mg mixed powder with a thickness of 15–53 µm for 3D printing.
[0028] According to the mass ratio of ZrO2:AlSi10Mg = 5:95, 50g of ZrO2 particles with an average particle size of 20nm and 950g of AlSi10Mg powder with a particle size range of 15-53µm were weighed out. The weighed AlSi10Mg powder and nano ZrO2 particles were placed in a three-dimensional mixer, and zirconia balls with an average particle size of 5mm were added at a ball-to-particle ratio of 1.5:1. Argon gas was introduced into the container for 1 minute, followed by mixing at a frequency of 24Hz for 3 hours. After the mixing process, the mixed powder was separated from the grinding balls. The mixed powder was placed in an acoustic resonance mixing container, and auxiliary hard balls with an average particle size of 2mm were added at a ball-to-particle ratio of 0.4:1, wherein the mass fraction ratio of tungsten balls to zirconia was 20%:80%. Argon gas was introduced into the container for 1 minute, followed by mixing for 15 minutes at an acceleration of 75g and a resonant frequency of 70Hz. After mixing, the mixed powder was separated from the grinding balls to obtain nanoparticle-modified aluminum alloy powder for 3D printing. Finally, the laser absorptivity of the mixed powder was measured. The morphology and properties of the spherical powder of this particle-reinforced aluminum matrix composite for 3D printing are as follows: Figure 3 , 4 As shown in Table 3.
[0029] Table 3. Properties of the 15–53 µm 5 wt.% ZrO2 / AlSi10Mg mixed powder prepared in Example 3 <![CDATA[5wt.%ZrO2 / AlSi10Mg]]> 1.54 80 12 Comparative Example 1
[0030] Prepare 0.5 wt.% ZrO2 / AlSi10Mg mixed powder. This comparative example does not include a premixing step, and the other steps are the same as in Example 1.
[0031] According to the mass ratio of ZrO2:AlSi10Mg = 0.5:99.5, 5g of ZrO2 particles with an average particle size of 20nm and 995g of AlSi10Mg powder with a particle size range of 15-53µm were weighed. The weighed AlSi10Mg powder and nano-ZrO2 particles were placed in an acoustic resonance mixing container. Auxiliary hard spheres with an average particle size of 0.3mm were added at a sphere-to-particle ratio of 0.4:1, wherein the mass fraction of tungsten spheres to zirconium oxide was 10%:90%. Argon gas was introduced into the container for 1 minute, followed by mixing for 10 minutes at an acceleration of 50g and a resonance frequency of 60Hz. After the mixing process, the mixed powder was separated from the grinding balls to obtain nanoparticle-modified aluminum alloy powder for 3D printing. Finally, the laser absorption rate of the mixed powder was measured. The morphology and properties of this spherical powder of particle-reinforced aluminum matrix composite for 3D printing are as follows: Figure 5 As shown in Table 4.
[0032] Table 4. Performance of 0.5 wt.% ZrO2 / AlSi10Mg mixed powder prepared in Comparative Example 1 <![CDATA[0.5wt.%ZrO2 / AlSi10Mg]]> 1.42 93 28 Compared to Example 1, Comparative Example 1 did not have a premixing step. The resulting mixed powder had severe agglomeration between some particles, which significantly reduced the particle dispersion and seriously affected the uniformity of nanoparticle distribution.
[0033] Comparative Example 2 Prepare a 0.5 wt.% ZrO2 / AlSi10Mg mixed powder. No hard spheres were added in this comparative example. Other steps were the same as in Example 1.
[0034] According to the mass ratio of ZrO2:AlSi10Mg = 0.5:99.5, 5g of ZrO2 particles with an average particle size of 20nm and 995g of AlSi10Mg powder with a particle size range of 15-53µm were weighed. The weighed AlSi10Mg powder and nano-ZrO2 particles were placed in a three-dimensional mixer, and zirconia balls with an average particle size of 5mm were added at a ball-to-particle ratio of 0.5:1. Argon gas was introduced into the container for 1 minute, followed by mixing at a frequency of 24Hz for 2 hours. After the mixing process, the mixed powder was separated from the grinding balls. The mixed powder was placed in an acoustic resonance mixing container, which was introduced with argon gas for 1 minute, followed by mixing at an acceleration of 50g and a resonance frequency of 60Hz for 10 minutes to obtain nanoparticle-modified aluminum alloy powder for 3D printing. Finally, the laser absorption rate of the mixed powder was measured. The morphology and properties of this spherical powder of particle-reinforced aluminum matrix composite for 3D printing are as follows: Figure 6 As shown in Table 5.
[0035] Table 5 Properties of the 15–53 µm 0.5 wt.% ZrO2 / AlSi10Mg mixed powder prepared in Comparative Example 2 <![CDATA[0.5wt.%ZrO2 / AlSi10Mg]]> 1.39 98 30 Compared to Example 1, Comparative Example 2 did not add hard spheres, and the resulting mixed powder contained more nanoparticle agglomerates, which seriously affected the uniformity of nanoparticle distribution. Comparative Example 3
[0036] Prepare 0.5 wt.% ZrO2 / AlSi10Mg mixed powder. In this comparative example, hard spheres with a particle size of 6 mm were selected. Other steps are the same as in Example 1.
[0037] According to the mass ratio of ZrO2:AlSi10Mg = 0.5:99.5, 5g of ZrO2 particles with an average particle size of 20nm and 995g of AlSi10Mg powder with a particle size range of 15-53µm were weighed. The weighed AlSi10Mg powder and nano ZrO2 particles were placed in a three-dimensional mixer, and zirconia balls with an average particle size of 5mm were added at a ball-to-particle ratio of 0.5:1. Argon gas was introduced into the container for 1 minute, followed by mixing at a frequency of 24Hz for 2 hours. After the mixing process, the mixed powder was separated from the grinding balls. The mixed powder was placed in an acoustic resonance mixing container, and auxiliary hard balls with an average particle size of 6mm were added at a ball-to-particle ratio of 0.4:1, wherein the mass fraction ratio of tungsten balls to zirconia was 10%:90%. Argon gas was introduced into the container for 1 minute, followed by mixing for 10 minutes at an acceleration of 50g and a resonant frequency of 60Hz. After mixing, the mixed powder was separated from the grinding balls to obtain nanoparticle-modified aluminum alloy powder for 3D printing. Finally, the laser absorptivity of the mixed powder was measured. The morphology and properties of the spherical powder of this particle-reinforced aluminum matrix composite for 3D printing are as follows: Figure 7 As shown in Table 6.
[0038] Table 6 Properties of the 15–53 µm 0.5 wt.% ZrO2 / AlSi10Mg mixed powder prepared in Comparative Example 3 <![CDATA[0.5wt.%ZrO2 / AlSi10Mg]]> 1.37 113 31 Compared to Example 1, the hard spheres in Comparative Example 3 had excessively large particle sizes, resulting in excessive kinetic energy during the preparation and mixing process, which led to matrix breakage and severely affected the integrity of the powder. Comparative Example 4
[0039] Prepare a 15wt.% ZrO2 / AlSi10Mg mixed powder. In this comparative example, the proportion of nanoparticles was adjusted to 15%, and the other steps were the same as in Example 1.
[0040] According to the mass ratio of ZrO2:AlSi10Mg = 15:85, 150g of ZrO2 particles with an average particle size of 20nm and 850g of AlSi10Mg powder with a particle size range of 15-53µm were weighed out. The weighed AlSi10Mg powder and nano ZrO2 particles were placed in a three-dimensional mixer, and zirconia balls with an average particle size of 5mm were added at a ball-to-particle ratio of 0.5:1. Argon gas was introduced into the container for 1 minute, followed by mixing at a frequency of 24Hz for 2 hours. After the mixing process, the mixed powder was separated from the grinding balls. The mixed powder was placed in an acoustic resonance mixing container, and auxiliary hard balls with an average particle size of 6mm were added at a ball-to-particle ratio of 0.4:1, wherein the mass fraction ratio of tungsten balls to zirconia was 10%:90%. Argon gas was introduced into the container for 1 minute, followed by mixing for 10 minutes at an acceleration of 50g and a resonant frequency of 60Hz. After mixing, the mixed powder was separated from the grinding balls to obtain nanoparticle-modified aluminum alloy powder for 3D printing. Finally, the laser absorptivity of the mixed powder was measured. The morphology and properties of the spherical powder of this particle-reinforced aluminum matrix composite for 3D printing are as follows: Figure 8 As shown in Table 7.
[0041] Table 7 Properties of the 15–53 µm 15 wt.% ZrO2 / AlSi10Mg mixed powder prepared in Comparative Example 4 <![CDATA[15wt.%ZrO2 / AlSi10Mg]]> 1.51 108 9 Compared to Example 1, Comparative Example 4 had an excessively high proportion of nanoparticles, which caused the particle coating layer to easily detach during the mixing process, severely affecting the uniformity of nanoparticle distribution. Comparative Example 5
[0042] Prepare 0.5 wt.% ZrO2 / AlSi10Mg mixed powder. In this comparative example, the acoustic resonance mixing time was adjusted to 2 min, and other steps were the same as in Example 1.
[0043] According to the mass ratio of ZrO2:AlSi10Mg = 0.5:99.5, 5g of ZrO2 particles with an average particle size of 20nm and 995g of AlSi10Mg powder with a particle size range of 15-53µm were weighed. The weighed AlSi10Mg powder and nano ZrO2 particles were placed in a three-dimensional mixer, and zirconia balls with an average particle size of 5mm were added at a ball-to-particle ratio of 0.5:1. Argon gas was introduced into the container for 1 minute, followed by mixing at a frequency of 24Hz for 2 hours. After the mixing process, the mixed powder was separated from the grinding balls. The mixed powder was placed in an acoustic resonance mixing container, and auxiliary hard balls with an average particle size of 0.3mm were added at a ball-to-particle ratio of 0.4:1, wherein the mass fraction ratio of tungsten balls to zirconia was 10%:90%. Argon gas was introduced into the container for 1 minute, followed by mixing for 2 minutes at an acceleration of 50g and a resonant frequency of 60Hz. After mixing, the mixed powder was separated from the grinding balls to obtain nanoparticle-modified aluminum alloy powder for 3D printing. Finally, the laser absorptivity of the mixed powder was measured. The morphology and properties of the spherical powder of this particle-reinforced aluminum matrix composite for 3D printing are as follows: Figure 9 As shown in Table 8.
[0044] Table 8 Properties of the 15–53 µm 0.5 wt.% ZrO2 / AlSi10Mg mixed powder prepared in Comparative Example 5 <![CDATA[0.5wt.%ZrO2 / AlSi10Mg]]> 1.41 94 29 Compared to Example 1, the acoustic resonance mixing time in Comparative Example 5 was too short, resulting in some nanoparticles not dispersing and severely affecting the uniformity of nanoparticle distribution.
[0045] The preferred embodiments of this patent have been described in detail, but this patent is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of this patent.
Claims
1. A method for preparing aluminum-based alloy powder for 3D printing with reinforcing particles embedded on its surface, characterized in that... The method specifically includes the following steps: Step 1: Weigh a certain proportion of matrix aluminum alloy component powder and nanoparticle reinforcing phase component powder, wherein the mass fraction ratio of the matrix aluminum alloy component powder and the nanoparticle reinforcing phase component powder is (95.0%~99.5%):(0.5%~5%). Step 2: Place the matrix aluminum alloy component powder and nanoparticle reinforced phase component powder weighed in Step 1 into a three-dimensional mixer, add zirconia balls with an average particle size of 5mm at a ball-to-particle ratio of 0.5~1.5:1, fill the tank with protective gas, and then mix at a frequency of 24Hz for 1~3h. After the mixing process is completed, separate the mixed powder from the grinding balls. Step 3: Place the mixed powder obtained in Step 2 into an acoustic resonance mixing tank, add auxiliary hard balls at a ball-to-powder ratio of 0.4:1, fill the tank with protective gas, and then mix for 8 to 15 minutes under an acceleration of 50 to 75g, with a resonance frequency of 60 to 70Hz. Step 4: Separate the acoustic resonance mixed powder from the grinding balls to obtain the target powder.
2. The method for preparing aluminum-based alloy powder for 3D printing with surface-embedded reinforcing particles according to claim 1, characterized in that: The matrix aluminum alloy component is selected from one of the following: 1-series aluminum alloys, 2-series aluminum alloys, 3-series aluminum alloys, 4-series aluminum alloys, 5-series aluminum alloys, 6-series aluminum alloys, 7-series aluminum alloys, 8-series aluminum alloys, and 9-series aluminum alloys; the nanoparticle reinforcing phase component is selected from one or more of the following: TiB2, LaB6, ZrC, B4C, SiC, TiC, WC, Al3BC, AlN, TiN, Si3N4, Al2O3, Y2O3, TiO2, SiO2, ZrO2, La2O3, and MgO.
3. The method for preparing aluminum-based alloy powder for 3D printing with surface-embedded reinforcing particles according to claim 1, characterized in that: In step one, the particle size of the matrix aluminum alloy component powder is 15~60μm, and the particle size of the nanoparticle-reinforced phase component powder is below 200nm.
4. The method for preparing aluminum-based alloy powder for 3D printing with surface-embedded reinforcing particles according to claim 1, characterized in that: In step two, the protective gas is argon.
5. The method for preparing aluminum-based alloy powder for 3D printing with surface-embedded reinforcing particles according to claim 1, characterized in that: In step three, the auxiliary hard spheres are one or more of tungsten, tungsten carbide, and zirconium oxide, with a particle size of 0.3~2mm.
6. The method for preparing aluminum-based alloy powder for 3D printing with surface-embedded reinforcing particles according to claim 1, characterized in that: In step three, the auxiliary hard spheres are composed of high-density tungsten or tungsten carbide spheres and low-density zirconium oxide spheres, wherein the mass fraction ratio of high-density hard spheres to low-density hard spheres is 10~20%:80~90%.
7. The method for preparing aluminum-based alloy powder for 3D printing with surface-embedded reinforcing particles according to claim 1, characterized in that: In step three, the protective gas is argon.
